1999
DOI: 10.1046/j.1432-1327.1999.00883.x
|View full text |Cite
|
Sign up to set email alerts
|

Conformations in solution of the fuscopeptins

Abstract: Fuscopeptins are phytotoxic amphiphilic lipodepsipeptides containing 19 amino acid residues. They are produced by the plant pathogenic bacterium Pseudomonas fuscovaginae in two forms, A and B, which differ only in the number of methylene groups in the fatty acid chain. Their covalent structure and biological properties have been reported previously. CD and NMR spectroscopy investigations in solution revealed the absence of identifiable elements of secondary and tertiary structure for these molecules. Fuscopept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 28 publications
(41 reference statements)
1
2
0
Order By: Relevance
“…CD and NMR spectroscopy revealed that FPs are completely unstructured in aqueous solution with a large molecular flexibility, while in a membrane mimetic solution the peptidic region appears to adopt a helical structure [40]. These results are in line with those reported for Tol where a prevalence of helical structure was indeed observed in lipid membrane [15].…”
Section: Planar Lipid Membrane Experimentssupporting
confidence: 88%
“…CD and NMR spectroscopy revealed that FPs are completely unstructured in aqueous solution with a large molecular flexibility, while in a membrane mimetic solution the peptidic region appears to adopt a helical structure [40]. These results are in line with those reported for Tol where a prevalence of helical structure was indeed observed in lipid membrane [15].…”
Section: Planar Lipid Membrane Experimentssupporting
confidence: 88%
“…Phylogenetic analysis of condensation domains allows to distinguish lipoinitiation (C start ), regular ( L C L ) and coepimerization (C/E) domains. This enabled a comparison of the inferred peptide stereochemistry with the reported structure of fuscopeptin (fuscopeptin A/B: C8/10-OH Dhb - (Ballio et al, 1996;Baréet al, 1999) and syringotoxin (syringotoxin B: C14-OH L-Ser -D-Dab -Gly -D-Hse -L-Orn -L-aThr -Z-Dhb -L-Asp(OH) -Cl-L-Thr) (Flamand et al, 1996;Bender et al, 1999) (Figure 1 and S3). The bioinformatic prediction matched well with the experimental data, except for the configuration of two fuscopeptin residues, L-Leu3 and D-Dab18.…”
Section: P Fuscovaginae Upb0736 Harbors Three Bgcs For the Production...mentioning
confidence: 99%
“…Both LPDs ( 14 and 15 ) showed phytotoxic and antifungal activity [ 31 ]. Their conformation in solution was also obtained by a NOE-NMR study [ 32 ].…”
Section: Source Isolation and Biological Activity Of Bacterial Lipode...mentioning
confidence: 99%